2023
DOI: 10.3389/fpubh.2023.1186442
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among healthcare students in Poland from COVID-19 to war on Ukraine: a cross-sectional exploratory study

Tomomi Hisato,
Shreya Nandy,
Eman M. Monga
et al.

Abstract: ObjectivesHealthcare students went through a rough time in March 2022 due to extreme changes in the educational system (moving from online to stationary learning) and Ukrainian-Russian war circumstances. Our study aims to update knowledge about psychological distress and its impact on healthcare students in Poland after two years of the COVID-19 pandemic, followed by intense and political instability in Europe.MethodsWe conducted a cross-sectional study on healthcare students from Poznan University of Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…However, the 2022 data obtained in the present research do not necessarily reflect mental health conditions solely due to the outbreak of war in Ukraine. Mental health problems may be associated with the COVID-19 pandemic, the unfavourable political and economic situation and fatigue from several years of crises (trauma/crisis fatigue) (Hisato et al, 2022), but also with past exposure to other types of trauma (Rzeszutek et al, 2023). A German study (Weierstall-Pust et al, 2022) showed that although the war in Ukraine and the climate crisis were rated as highly stressful, the COVID-19 pandemic had a significantly more negative impact on psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the 2022 data obtained in the present research do not necessarily reflect mental health conditions solely due to the outbreak of war in Ukraine. Mental health problems may be associated with the COVID-19 pandemic, the unfavourable political and economic situation and fatigue from several years of crises (trauma/crisis fatigue) (Hisato et al, 2022), but also with past exposure to other types of trauma (Rzeszutek et al, 2023). A German study (Weierstall-Pust et al, 2022) showed that although the war in Ukraine and the climate crisis were rated as highly stressful, the COVID-19 pandemic had a significantly more negative impact on psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The two countries also share a common historical experience. The psychological crisis in Poles after Russia's invasion of Ukraine was a result of an overlap of many factors (the COVID-19 pandemic, internal political changes and the deterioration of the economic situation, the fear of Russian aggression against Poland) (Centrum Badania Opinii Społecznej, 2023;Hisato et al, 2022;Kacprzak, 2023;Laboratorium Badań Medioznawczych UW, 2022). Comparative analyses of populations from Ukraine, Taiwan and Poland (March 2022) indicated that more than 80% of Poles were concerned about the situation in Ukraine as described in the media, 52.8% followed current news reports for more than an hour a day, and 57.2% presented with clinical manifestations of PTSD.…”
Section: Introductionmentioning
confidence: 99%